Comparison of the chemical composition and antioxidant, anti-inflammatory, α-amylase and α-glycosidase inhibitory activities of the supernatant and cream from black tea infusion. Issue 11 (17th May 2022) - Qin, Chunyin; Lian, Li; Xu, Wen; Jiang, Zongde; Wen, Mingchun; Han, Zisheng; Zhang, Liang
Abstract : Tea cream is a kind of turbid substance commonly existing in tea infusion and tea beverage upon cooling. Abstract : Tea cream is a kind of turbid substance commonly existing in tea infusion and tea beverage upon cooling. Herein, a comparative study was conducted on the supernatant and cream from black tea infusion in terms of antioxidant, anti-inflammatory and enzyme inhibitory activities, and chemical composition. Ultraviolet–visible (UV–vis) spectrometry and high-performance liquid chromatography (HPLC) analysis showed that the contents of protein, polyphenols, theaflavins, thearubigins, theabrownins, and caffeine in cream were significantly higher than those in the supernatant. The contents of Al, Ca, Cu, and Fe elements in cream were higher than those in the supernatant. However, higher levels of monosaccharides and free amino acids were detected in the supernatant compared with cream. The ultra-performance liquid chromatography quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF-MS) based metabolomics analysis revealed that the main marker compounds between the supernatant and the cream were organic acids, phenolic acids, and flavan-3-ols and their oxidation products, flavonol glycosides and amino acids. The cream showed better antioxidant and anti-inflammatory, as well as α-amylase and α-glycosidase inhibitory activities than the supernatant, because it contained higher contents of polyphenols than the supernatant. The present study expanded the new vision towards the cream of black tea infusion.